DIGITAL CONFIDENCE ENVIRONMENT IN PROCEDURE RELATIONSHIPS - Kh. Valeev, Damir; G. Nuriev, Anas (Gênero & Direito, 2019)
The implementation of the legally proclaimed ideas and principles is ensured by the mechanism of intersectoral regulators which, being in constant relationship contribute to the solution of tasks set. But the mechanism established at the level of legal regulators cannot be isolated from the environment in which certain rules of conduct should be guided. This is due to the possible “artificiality” of the rules of behaviour, which can be expressed either in the fact that the rule exists, but there are no really existing social relations that can fall under the regulatory influence in this sector, or statutory regulators no longer meet the needs of social development due to their inability to regulate actually existing relations. All this determines the importance of studying the environment in which the system of statutory regulators will be created to achieve a specific goal and task. The strategy for the development of the information society in the Russian Federation for 2017 - 2030 defines the development of the information society as the goal and objective of the application of information and communication technologies. The construction of the information society, which will exist within the framework of the "electronic state", involves the "digitalization" of all sections of public relations, including such an important area as the administration of justice. Thus, the digital environment should also organically include procedural relationships that make it possible to exist